JOURNEY THROUGH THE PAGES: EXPLORING THE RICH TAPESTRY OF ENGLISH LITERATURE - Rahmat Purnomo (Journal of Linguistica, 2024)
This article explores the wealth of English literature, offering diverse narratives spanning centuries. From epic poetry to modern novels, we understand the evolution of English literature and its impact on global culture. The article delves into themes, styles, and voices enriching the landscape of English literature, as well as its role in reflecting and shaping society. The research method employed is qualitative, utilizing literature review and historical research. With this approach, the researcher analyzes literary texts alongside their historical and cultural contexts. The discussion underscores the importance of English literature in capturing human experiences and prompting readers for personal reflection and deeper understanding of the world. The conclusion asserts that journeying through the pages of English literature is a rich and profound experience, enriching our understanding of humanity and the world around us.